Nel mondo degli Slavi. Incontri e dialoghi tra culture. Studi in onore di Giovanna Brogi Bercoff - Di Salvo, Maria Giovanna; MORACCI, Giovanna; SIEDINA, Giovanna (Biblioteca di Studi Slavistici, 2008)
This book is a tribute to Giovanna Brogi Bercoff, Full Professor of History of Russian at the State University of Milan and a leading authority on Polish studies, mediaeval Russian literature and Ukrainian studies, both in Italy and abroad. Former Chairman of the Associazione Italiana degli Slavisti, she contributed to project Italian Slavic studies into an international dimension. Among the most significant aspects of her intense academic and teaching career we should mention the pioneering studies on historiography and the Baroque culture in the Slavic area, as well as the introduction of Ukrainian studies at the University of Milan. The authors of the essays collected here, which range from linguistics to philology, and from literary theory to history, are Italian and foreign scholars of different generations and different cultural backgrounds.